Berpikir Matematis dalam Menyelesaikan Soal Barisan Dan Deret Aritmetika Ditinjau Dari Kecemasan Matematika - Auliaul Haque; Masriyah; Endah Budi Rahaju (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The study aims to describe the mathematical thinking process of students who have low, medium, and high levels of math anxiety in solving arithmetic sequence and Series problems. This study is a descriptive qualitative research. The data collection method used math anxiety tests, math ability tests, thought process tests, and interviews to determine students ' thought processes. The subjects of the study consisted of three high school XI female students with equivalent mathematical ability that is medium. The ability of students is measured using a math ability test that contains questions related to Class X material. Students with low anxiety solved the problem well and were full of confidence that the answers given were correct. Students with anxiety are solving problems well despite some mistakes and a little doubt about the answers given. Students with anxiety are solving problems with some errors and are not confident that the answers given are correct